Analyzing students’ mathematical communication skills based on their self-efficacy during the Covid-19 pandemic - Sholihah, Nur; Istihapsari, Vita; Santosa, Imam (International Journal on Education Insight, 2022)
This study aims to analyze students' mathematical communication skills based on their self-efficacy during the covid-19 pandemic. The method used is descriptive qualitative. The population was VII grade students of SMP Negeri 1 Bantul. The purposive sampling technique was used to select samples. The subject was grouped based on their self-efficacy with high, medium, and low categories to be tested and interviewed about their mathematical communication skills. The instrument in this study was a self-efficacy questionnaire, a test of mathematical communication skills, and an interview guideline. The triangulation technique was carried out by comparing the mathematical communication skills test results with the interview. The result of mathematical communication skills during the Covid-19 pandemic are not in line with their level of self-efficacy. High self-efficacy does not necessarily make students have high mathematical communication skills. The factor causing the misalignment is the fact that the online learning process carried out during the Covid-19 pandemic does not enough facilitate students to hone their mathematical communication skills, both oral and written.